Autophagy-dependent ferroptosis contributes to cisplatin-induced hearing loss. (10th October 2021) - Jian, Bingquan; Pang, Jiaqi; Xiong, Hao; Zhang, Weijian; Zhan, Ting; Su, Zhongwu; Lin, Hanqing; Zhang, Huasong; He, Wuhui; Zheng, Yiqing
Highlights: Ferroptosis is one of the auditory cell death forms under cisplatin injury. The activation of the specific autophagy pathway, ferritinophagy, is required for ferroptosis execution in HEI−OC1 cells. Ferroptosis inhibitor ameliorates the hearing impairment in C57BL/6 mice and outer hair cells loss after cisplatin exposure. Abstract: Cisplatin-induced hearing loss is a common side effect of cisplatin chemotherapy, for which clinical therapy remains unavailable. Apoptosis of hair cells is considered the primary cause of cisplatin-induced ototoxicity; however, inhibiting apoptosis can only partially restore cisplatin-induced hearing loss. Therefore, auditory cell death caused by cisplatin damage requires further study. Ferroptosis, a novel form of regulated cell death, has been shown to play a role in the mechanism of cisplatin toxicity. In this study, we observed proferroptotic alterations (lipid peroxidation and impaired antioxidant capacity) in the cochleae of C57BL/6 mice after cisplatin damage, verifying the induction of ferroptosis. Using the HEI−OC1 cell line, we observed that cisplatin induced proferroptotic alterations and activated ferritinophagy (specific autophagy pathway). Employing chloroquine, we confirmed that the blockage of autophagy remarkably alleviated cisplatin-induced ferroptosis in HEI−OC1 cells; therefore, the induction of ferroptosis in cisplatin-treated auditory cells was dependent on the activation of autophagy. In addition, the ferroptosis inhibitor ferrostatin-1 and iron chelator deferoxamine significantly attenuated cisplatin-induced cytotoxicity in HEI−OC1 cells and cochlear explants. Moreover, pharmacologically inhibiting ferroptosis using ferrostatin-1 significantly decreased the auditory cell loss and, notably, attenuated hearing loss in C57BL/6 mice after cisplatin damage. Collectively, these findings indicate that autophagy-dependent ferroptosis plays an integrated role in the mechanism of cisplatin-induced hearing loss.